An insight into gingival depigmentation techniques: The pros and cons - Alasmari, Dhafer S. (International Journal of Health Sciences, 2018)
Pigmentation of gingiva not just has an impact on esthetics but also creates psychological negativity. Although a wide array of depigmentation techniques are available to manage this condition, there is a scarcity of literature that guides clinicians to choose the most appropriate technique. Hence, the aim of this review is to evaluate the available depigmentation therapeutic modalities with an emphasis on their merits and demerits. The databases of MEDLINE and Cochrane databases of systematic reviews were searched to collect relevant scientific literature. Cryosurgery followed by lasers has been reported to be the superior techniques with better esthetic results and low rate of recurrence. However, further randomized controlled longitudinal studies are warranted to elaborate the efficiency and effectiveness of available techniques.